Differences in the intrahepatic expression of immune checkpoint molecules on T cells and natural killer cells in chronic HBV patients - Dumolard, Lucile; Hilleret, Marie-Noelle; Costentin, Charlotte; Mercey-Ressejac, Marion; Sturm, Nathalie; Gerster, Theophile; Decaens, Thomas; Jouvin-Marche, Evelyne; Marche, Patrice N.; Macek Jilkova, Zuzana (Frontiers in Immunology, 2025)
BackgroundPatients with chronic hepatitis B virus (HBV) infection are characterized by impaired immune response that fails to eliminate HBV. Immune checkpoint molecules (ICMs) control the amplitude of the activation and function of immune cells, which makes them the key regulators of immune response.MethodsWe performed a multiparametric flow cytometry analysis of ICMs and determined their expression on intrahepatic lymphocyte subsets in untreated and treated patients with HBV in comparison with non-pathological liver tissue.ResultsThe liver of untreated HBV patients exhibited a high accumulation of PD-1+CD8+ T cells, while the frequencies of 4-1BB+ T cells, 4-1BB+ natural killer (NK) cells, and TIM-3+CD8+ T cells were the highest in the chronic hepatitis phase. Our findings showed that the HBeAg status is linked to a distinct immune phenotype of intrahepatic CD8+ T cells and NK cells characterized by high expression of ICMs, particularly 4-1BB. Importantly, antiviral treatment partially restored the normal expression of ICMs. Finally, we described important differences in ICM expression between intrahepatic and circulating NK cells in HBV patients.ConclusionsOur study shows clear differences in the intrahepatic expression of ICMs on NK cells and T cells in chronic HBV patients depending on their clinical stage.